2020
DOI: 10.1016/j.ajoc.2020.100814
|View full text |Cite
|
Sign up to set email alerts
|

Pseudophakic adult with progressive optic disc tilt and axial length elongation

Abstract: Purpose To describe a case of progressive optic disc tilt in a pseudophakic Asian adult associated with an increase in axial length. Observations A 28-year-old man presented with high myopia in the right eye with an axial length of 30.4 mm and refraction of −13.75 diopters (D) spherical equivalent (SE). The refraction was plano sphere after LASIK and LASIK enhancement. The left eye was blinded by retinal detachment after phacoemulsification. Six years later, the right e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Optic disc tilt is usually associated with myopic elongation of the eye globe and deformation of the optic disc and peripapillary sclera,10,11 processes that may affect RNFL thickness. RNFL was shown to be thinner in healthy eyes with than without optic disc tilt 12.…”
Section: Discussionmentioning
confidence: 99%
“…Optic disc tilt is usually associated with myopic elongation of the eye globe and deformation of the optic disc and peripapillary sclera,10,11 processes that may affect RNFL thickness. RNFL was shown to be thinner in healthy eyes with than without optic disc tilt 12.…”
Section: Discussionmentioning
confidence: 99%
“…In myopia, morphological changes of the optic disk such as formation of peripapillary atrophy (PPA) and optic disk tilt occur ( 11 , 12 ). PPA formation and disk tilting are known to be accompanied by mechanical scleral stretching and posterior deformation secondary to axial elongation ( 13 , 14 ). In addition, a recent study ( 15 ) found that retinal microvasculature of macular and peripapillary regions was significantly reduced according to the degree of optic nerve head deformations in highly myopic eyes.…”
Section: Introductionmentioning
confidence: 99%